Services for Pregnant Women at Ahmad Berahim General Hospital, Tana Tidung Regency - Herni, Herni; Muhtar, Entang Adhy; Wardiny, Tuty Maria (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2025)
Efforts to improve the quality of public services are essential to ensure the fulfillment of basic rights of the community, including in the health sector, which is one of the key indicators in building superior and competitive human resources. This study aims to analyze the quality of health services for pregnant women at Akhmad Berahim Hospital, Tana Tidung Regency through five dimensions of SERVQUA: tangible, reliability, responsiveness, assurance, and empathy. The research method used is qualitative descriptive with data collection techniques through observation, interviews and documentation. Interviews were conducted with informants who have the power of knowledge regarding the research objectives. Meanwhile, the data analysis techniques used are data reduction, data presentation, and conclusion drawn. The results of the analysis show that the service is quite good, with adequate physical facilities, professional medical personnel, and affordable cost policies. However, several challenges need to be overcome, such as the limited number of medical personnel, especially specialist doctors, and the need to improve facilities, including air conditioning and medical equipment for the diagnosis of complications. The reliability and assurance dimensions show positive achievements through the implementation of good SOPs, service time efficiency, and the competence of medical personnel that create a sense of security for patients. Responsiveness can be seen from clear service information, although it still needs improvement to meet complex patient needs. The empathetic attitude of medical staff and the free milk program help increase patient satisfaction and create positive relationships